Minimal vascular flows cause strong heat sink effects in hepatic radiofrequency ablation ex vivo. (28th July 2016) - Lehmann, Kai S.; Poch, Franz G.M.; Rieder, Christian; Schenk, Andrea; Stroux, Andrea; Frericks, Bernd B.; Gemeinhardt, Ole; Holmer, Christoph; Kreis, Martin E.; Ritz, Jörg P.; Zurbuchen, Urte
Abstract: Background: The present paper aims to assess the lower threshold of vascular flow rate on the heat sink effect in bipolar radiofrequency ablation (RFA) ex vivo. Methods: Glass tubes (vessels) of 3.4 mm inner diameter were introduced in parallel to bipolar RFA applicators into porcine liver ex vivo. Vessels were perfused with flow rates of 0 to 1, 500 ml/min. RFA (30 W power, 15 kJ energy input) was carried out at room temperature and 37°C. Heat sink effects were assessed in RFA cross sections by the decrease in ablation radius, area and by a high‐resolution sector planimetry. Results: Flow rates of 1 ml/min already caused a significant cooling effect ( P ≤ 0.001). The heat sink effect reached a maximum at 10 ml/min (18.4 mm/s) and remained stable for flow rates up to 1, 500 ml/min. Conclusions: Minimal vascular flows of ≥1 ml/min cause a significant heat sink effect in hepatic RFA ex vivo. A lower limit for volumetric flow rate was not found. The maximum of the heat sink effect was reached at a flow rate of 10 ml/min and remained stable for flow rates up to 1, 500 ml/min. Hepatic inflow occlusion should be considered in RFA close to hepatic vessels. Abstract : Highlight Lehmann and colleagues set out to determine the cooling effect of liver perfusion during radiofrequency ablation, which can lead to tumor recurrence. Surprisingly, even minimal flows of 1 ml/min caused a significant cooling effect ex vivo. They conclude that inflow occlusion should be considered in radiofrequency ablation close to hepatic vessels.